Bioseguridad en el personal de salud de neonatología del Hospital General Isidro Ayora - Cosíos Carreño, Oscar Isaac (2015)
Although the theme of biosafety has been widely discussed internationally, there are no scientific publications that provide relevant quantitative and qualitative information on the implementation of biosafety standards in a specific way in neonatology services in different health institutions of our country. This research entitled “BIOSAFETY OF THE HEALTH PERSONNEL THAT WORKS IN THE NEONATOLOGY SERVICE OF THE GENERAL HOSPITAL ISIDRO AYORA” this research was descriptive, and aims to characterize the knowledge and practices of Biosafety of the health personnel that works in the Neonatology Service of the General Hospital Isidro Ayora. To meet this objectiv a survey supported in a questionnaire and an observation guide were applied; the universe is made up of 69 persons that constitute the health personnel that work in the Neonatology Service of the General Hospital Isidro Ayora. Some of the results after applying the data collection tools were: 33.3% of health workers know the definition of biosafety and 59.4% do not know the principles of biosafety. Besides, 66.7% of health workers do not know the order of steps for handwashing and 40.6% use long nails, nail polish or accessories, also 65.2% of health personnel practice the maneuver of recapping the needle and 88.4% use the phone in the workplace, although biosafety standards restrict its use in critical areas. KEYWORDS: Knowledge, Practice, Biosafety. Neonatology.